Fear or freedom? Visually impaired students' ambivalent perspectives on physical education. (January 2021) - Ruin, Sebastian; Giese, Martin; Haegele, Justin A
With a growing interest in sport, fitness, and a healthy lifestyle, bodily practices are increasing in importance in our society. In the school context, physical education (PE) is the subject where these practices play a central role. But, the German language discourse shows in an exemplary manner that inherent body-related social normality requirements are articulated in didactic traditions and curricular requirements, and that these normality requirements have exclusionary potential for those students who do not fit into the norms. Against this background, this article seeks to understand children with visual impairments' (CWVI's) individual constructions of PE in a school specialized for CWVI in Germany. This interview study with eight CWVI focused on individual opportunities and challenges concerning central aspects in PE. The findings show that the CWVI draw ambivalent perspectives on PE that range from existential fears (e.g., fears of heights) to feeling free in working off energy. These aspects especially gain importance in connection to the body, when the general wish to learn and experience with the body seems to be disturbed by normality requirements – like doing certain movements in a pre-defined way – which lead to existential challenges for the CWVI. Further, the relationship between blind and visually impaired students in PE seems ambivalent. Within this special school setting, the segregation according to the external differentiation in "handicapped" and "non-handicapped" somehow leads to a kind of subsegregation at the blind and visually impaired school.